Effect of Physical Activity, Social Support and Skills Training on Late-Life Emotional Health: A Systematic Literature Review and Implications for Public Health Research - Mark B. Snowden; Lesley eSteinman; Whitney L. Carlson; Kara N. Mochan; Ana F. Abraido-Lanza; Lucinda L. Bryant; Michael eDuffy; Bob G. Knight; Dilip V. Jeste; Katherine H. Leith; Eric J. Lenze; Rebecca G. Logsdon; et al. (Frontiers in Public Health, 2015)
.